2009
DOI: 10.1152/physiolgenomics.00003.2008
|View full text |Cite
|
Sign up to set email alerts
|

KIF5B gene sequence variation and response of cardiac stroke volume to regular exercise

Abstract: A genome-wide linkage scan for endurance training-induced changes in stroke volume detected a quantitative trait locus on chromosome 10p11 in white families of the HERITAGE Family Study. Dense microsatellite mapping narrowed down the linkage region to a 7 Mb area containing 16 known and 14 predicted genes. Association analyses with 90 single nucleotide polymorphisms (SNPs) provided suggestive evidence (P values from 0.03 to 0.06) for association in the kinesin heavy chain (KIF5B) gene locus in the whole cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Both traits are characterized by increased incidence of cardiac events during exercise. The positional cloning efforts of the response to exercise QTLs in the HERITAGE Family Study have yielded a number of strong candidates for the changes in submaximal exercise capacity with regular exercise ( CREB1 ) and in SV and Q ( KIF5B ) (16, 253). …”
Section: Identifying Genes Sequence Variants and Other Genomic Markersmentioning
confidence: 99%
“…Both traits are characterized by increased incidence of cardiac events during exercise. The positional cloning efforts of the response to exercise QTLs in the HERITAGE Family Study have yielded a number of strong candidates for the changes in submaximal exercise capacity with regular exercise ( CREB1 ) and in SV and Q ( KIF5B ) (16, 253). …”
Section: Identifying Genes Sequence Variants and Other Genomic Markersmentioning
confidence: 99%
“…The QTL on 10p11 for the gains in stroke volume was narrowed down to a 7 Mb region. Among the linkage-positive families, the strongest associations were found with single nucleotide polymorphisms (SNPs) in the kinesin family member 5B ( KIF5B ) gene locus (41). Resequencing of KIF5B revealed several sequence variants.…”
Section: Genetics and Response To Regular Exercisementioning
confidence: 99%
“…The SNP with the strongest association modified the KIF5B promoter activity in cell-based systems. Furthermore, inhibition and overexpression studies in C2C12 cells showed that changes in KIF5B expression level altered mitochondrial localization and biogenesis; KIF5B inhibition led to diminished biogenesis and perinuclear accumulation of mitochondria, while overexpression enhanced mitochondrial biogenesis (41). …”
Section: Genetics and Response To Regular Exercisementioning
confidence: 99%
“…9,10 These previous studies used the same approach as the present study: They first found significant heritability for the phenotype of interest, identified novel loci potentially underlying this phenotype using genome-wide linkage analyses, fine mapped the chromosomal locus with the highest linkage, performed numerous SNP statistical association analyses, and performed cell culture studies to assess the molecular effects of their novel SNPs. In both previous studies, the phenotype of interest was the traininginduced change in submaximal exercise stroke volume, and the novel genes that they identified were titin 10 and kinesin-1 heavy chain.…”
Section: Article See P 294mentioning
confidence: 99%
“…In both previous studies, the phenotype of interest was the traininginduced change in submaximal exercise stroke volume, and the novel genes that they identified were titin 10 and kinesin-1 heavy chain. 9 Neither of these 2 genes would have been considered candidate chromosomal loci to underlie this phenotype. Similarly, cAMP responsive element binding protein 1, found to play such an important role in the present study, would not have been on any list as a potential candidate gene affecting the training-induced change in submaximal exercise HR.…”
Section: Article See P 294mentioning
confidence: 99%